Knowledge of PCOS in physicians-in-training: identifying gaps and educational opportunities. (2nd October 2020) - Chemerinski, Anat; Cooney, Laura; Shah, Divya; Butts, Samantha; Gibson-Helm, Melanie; Dokras, Anuja
Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in reproductive-aged women. A recent study found that many obstetrics and gynecology (ObGyn) practicing physicians are unaware of the Rotterdam criteria recommended for diagnosis. Our objective was to identify gaps in trainee knowledge of PCOS diagnostic criteria and management. An online survey was sent out to US ObGyn physicians-in-training in 2018. The primary outcomes were identification of at least one component of each Rotterdam criteria (Rot-3): (1) oligomenorrhea/amenorrhea, (2) clinical or biochemical hyperandrogenism, and (3) ovarian volume or antral follicle count, and identification of all five components (Rot-5). Secondary outcomes were identification of comorbidities and management of PCOS. Multivariable logistic regression was used controlling for gender, seniority (PGY) status, program type, completion of an REI rotation, and number of PCOS patients seen. 85.4% of 347 trainees completing the survey reported using Rotterdam criteria to diagnose PCOS. However, only 55% identified Rot-3 and less than 10% identified Rot-5. Seniority (PGY4 OR 2.2; 95% CI: 1.2–4.1; p  = .01) and completion of REI rotation (OR 1.8 95% CI: 1.2, 1.8; p  = .006) were associated with identifying Rot-3. Similar findings were noted with identifying Rot-5. Our study identified significant gaps in knowledge regarding PCOS, suggesting an urgent need for improving strategies for trainee education to increase patient satisfaction and provide comprehensive care.